Industrial Zones: A Successful Agglomeration Form in Morocco - Taking the Marrakech Cluster as An Example - Saranya, Mamadou (Journal of Global Economy, Business and Finance, 2024)
This article aims to investigate the experience of clustering policy adopted by Morocco and demonstrate the positive effects of this agglomeration on the development of a given sector. For our study, we chose the case of the Menara Cluster based in the city of Marrakech, specializing in agri - food and cosmetics. Our theoretical study allows us to classify the cluster as an industrial district, upon which we shed light on the success of this policy.